A study of methods to enhance infrared emissivity of Molybdenum surfaces - Alekseev, Andrey; Andreenko, Evgeny; Orlovskiy, Ilya; Gorshkov, Aleksey; Akhtyrsky, Sergey; Kozlov, Andrey; Smekalin, Viktor; Ulyanitskiy, Vladimir; Khmelnitsky, Roman; Evlashin, Stanislav; Eberle, Sebastian (Fusion engineering and design, 2019)
Single crystal Molybdenum is one of the most promising materials for the First Mirror (FM) of ITER optical diagnostics due to its high resistance to erosion under neutral atom bombardment. Other advantages are: low CTE, high thermal conductivity, and advantageous mechanical properties at elevated temperatures. The FMs are normally located in the front-end of ITER port plugs, being subject to volumetric heat loads up to ∼1 W/cm3 and higher. Active cooling of Mo mirrors by water or gas flow has limited applicability due to remote handling, integration and risk requirements. An athermal design with radiative cooling was developed for the H-alpha FM unit (FMU) with an all-Mo/TZM structure comprising a TZM housing, two Mo mirrors and the TZM cleaning electrodes. The main idea is to minimize mirror angular displacements and to keep the alignment at temperatures up to ∼350 °C. That requires a balance between thermal contact and radiative heat sinks. The most uniform temperature profile is obtained by weak thermal contact between FMU and support structure, but that leads to the highest FM temperature, since the normal as-milled Mo surface has a very low effective emissivity (ε < 0.1 at 200…400 °C). Well-known tools for surface blackening are: enhanced roughness, oxidation, V-grooving, and coatings, which should be analyzed for outgassing rate, thermal radiation and long-term stability in Hydrogen environment. In this study, a number of techniques to enhance Mo surface effective emissivity were tested: V-grooving, detonation spray coating, drilling and surface electro-erosion. Spectral emissivity of the test samples was measured by Bruker Vertex-70 infrared Fourier spectrometer and the effective values were derived for subsequent thermal analyses. Alumina coatings were found to be the most effective tool with ε ≈ 0.8…0.9. However, V-grooving and drilling also provide acceptable results (εeff ≈ 0.25…0.3) and do not require qualification for applicability to ITER. The trade-off between different techniques is discussed in detail.